Labubu's Adaptation in the Practice of Christian Religious Education Curriculum for Generation Alpha - Roce Marsaulina; Gilbert Timothy Majesty (International Journal of Christian Education and Philosophical Inquiry, 2025)
Generation Alpha is growing up in an era dominated by rapid technological advancement and digital interaction, which necessitates the development of innovative, engaging, and interactive learning strategies. This need extends to Christian Religious Education (CRE), where traditional methods may no longer fully capture the attention or meet the learning styles of today's children. One promising approach is the adaptation of Labubu dolls as a learning medium within the CRE curriculum. With their distinctive, expressive features, Labubu dolls can serve as an effective pedagogical tool to convey Christian values in a manner that is both relatable and captivating for young learners. This article explores the integration of Labubu dolls into Christian Religious Education as a medium to enhance student engagement, comprehension, and internalization of core religious values. Using a qualitative research design with a constructivist approach, the study investigates how puppetry, particularly through Labubu dolls, can transform abstract theological ideas into concrete, child-friendly learning experiences. Data was collected through observation, interviews, and reflective practices involving teachers and students in early education settings. Findings indicate that the incorporation of storytelling, character interaction, and reflective dialogue facilitated by Labubu dolls significantly improves children's understanding of Christian principles. The dolls create a dynamic learning environment that encourages emotional connection, moral reasoning, and active participation. Furthermore, the playful yet structured nature of puppet-based instruction aligns well with the cognitive and emotional development of Generation Alpha, making it a highly relevant educational innovation. In conclusion, the use of Labubu dolls within the Christian Religious Education curriculum represents a strategic response to contemporary educational challenges. It not only enhances pedagogical effectiveness but also supports the formation of Christian character and faith from an early age, positioning Labubu dolls as a transformative medium for religious instruction in the digital age.